SOCIOLOGICAL AND ANTHROPOLOGICAL STUDIES OF STUNTING FAMILIES STUNTING IN MALANG REGENCY - I Dewa Nyoman Supariasa; Ibnu Fajar; Sugeng Iwan S; Khairuddin Khairuddin (Proceeding B-ICON, 2022)
Stunting is a failed growth in toddlers as a result of chronic nutritional deficiency occurring during the first 1000 days of life making children too short for their age. Toddlers stunting prevalence nationally in 2013 was 37.2%, increasing from 2010 (35.6%) and 2007 (36.8%). In Malang Regency, toddlers stunting prevalence had an increase in the first three years and a decrease in the last two years of 2012—2016 periods, with highest prevalence 30.6% in 2014 and lowest 22.9% in 2016. The current study aimed to analyze the sociological and anthropological characteristics of families with stunted toddlers in Malang Regency. Applying qualitative research design, 33 participants from 3 stunting locus villages of Ngawonggo, Dilem and Karangsari in Malang Regency were involved to represent the urban, highland and coastal areas. Participants for focused group discussion were 15 authoritative figures from the villages. The majority of 26 (78.7%) pregnant mothers ate 3 times per day, but only 8 mothers (24.2%) had complete variety of food consumption during pregnancy. Some food mothers were restricted to eat during pregnancy prescribed by their old belief system were sea fish, kelotok fish, stink beans, pineapples, durians. The majority of 93% toddlers received breast milk feeding. Regarding toddlers’ energy consumption, 69.7 had excess protein intake, 39.39 had severe deficit fat intake, 87.88 had severe deficit carbohydrate intake. On mothers’ nutritional knowledge, 15.1% participants were in good level, 30.3% adequate, and 45.5% inadequate. Regarding hygiene and sanitation, 81.82% observed households had home toilets, but 18.18% had not. 18.82 households consumed boiled tap water for drinking, and 18.18% bought gallon packaged. Sociological and anthropological factors, namely mothers’ eating habits during pregnancy, dietary restrictions, nutritional knowledge, toddlers eating patterns, home hygiene and sanitation, influenced toddlers stunting incidents.